Postoperative Acute Pancreatitis Following Pancreaticoduodenectomy: A Determinant of Fistula Potentially Driven by the Intraoperative Fluid Management. Issue 5 (November 2018) - Bannone, Elisa; Andrianello, Stefano; Marchegiani, Giovanni; Masini, Gaia; Malleo, Giuseppe; Bassi, Claudio; Salvia, Roberto
Abstract : Objective: The aim of the study is to characterize postoperative acute pancreatitis (POAP). Summary Background Data: A standardized definition of POAP after pancreaticoduodenectomy (PD) has been recently proposed, but specific studies are lacking. Methods: The patients were extracted from the prospective database of The Pancreas Institute of Verona. POAP was defined as an elevation of the serum pancreatic amylase levels above the upper limit of normal (52 U/L) on postoperative day (POD) 0 or 1. The endpoints included defining the incidence and predictors of POAP and investigating the association of POAP with postoperative pancreatic fistula (POPF). Results: The study population consisted of 292 patients who underwent PD. The POAP and POPF rates were 55.8% and 22.3%, respectively. POAP was an independent predictor of POPF (OR 3.8), with a 92% sensitivity and 53.7% specificity (AUC 0.79). Preoperative exocrine insufficiency (OR 0.39), neoadjuvant therapy (OR 0.29) additional resection of the pancreatic stump margin (OR 0.25), soft pancreatic texture (OR 4.38), and Main Pancreatic Duct (MPD) diameter ⩽3 mm (OR 2.86) were independent predictors of POAP. In high-risk patients, an intraoperative fluid administration of ⩽3 ml/kg/h was associated with an increased incidence of POAP (24.6 vs. 0%, P = 0.04) and POPF (27.6 vs. 11.4%, P = 0.05). Conclusion: This study represents the first clinical application of the only available definition of POAP as a specific complication of pancreatic surgery. POAP is associated with an increased occurrence of POPF and overall morbidity and could potentially be avoided through a specific intraoperative fluid regimen in high-risk pancreas. Abstract : Supplemental Digital Content is available in the text